2019
DOI: 10.1089/aut.2018.0023
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Diagnostic Validity of Autism Measures Among Adults in an Outpatient Clinic Sample

Abstract: Background: Previous research has questioned the validity of diagnostic measures for autism spectrum disorder (ASD) among adults. This study examined the correspondence between several measures and clinician diagnosis. Methods: We conducted a retrospective chart review for 93 adults (18-61 years; 72% male) who received an ASD evaluation at a specialty outpatient clinic. Thirty-one individuals (33%) in the sample were diagnosed with ASD. We compared participant scores on the Autism Spectrum Quotient (AQ), the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
1
26
2
Order By: Relevance
“…The respondent determines the extent to which a symptom is Sizoo et al (2015), study (clinical setting, adults suspected of ASD, ASD rate = 66%) not included here, since it does not concern AQ-50, but AQ-10 and AQ-28. Conner et al (2019) had a non-ASD groups that scored higher than the ASD group on the AQ: this finding is remarkably different from all other studies reported here ACC accuracy (correct classification), ANX NA personally applicable on a 4-point Likert-scale: 'definitely agree', 'slightly agree', 'slightly disagree', and 'definitely disagree'. All answers are dichotomized for processing.…”
Section: Instrumentscontrasting
confidence: 99%
“…The respondent determines the extent to which a symptom is Sizoo et al (2015), study (clinical setting, adults suspected of ASD, ASD rate = 66%) not included here, since it does not concern AQ-50, but AQ-10 and AQ-28. Conner et al (2019) had a non-ASD groups that scored higher than the ASD group on the AQ: this finding is remarkably different from all other studies reported here ACC accuracy (correct classification), ANX NA personally applicable on a 4-point Likert-scale: 'definitely agree', 'slightly agree', 'slightly disagree', and 'definitely disagree'. All answers are dichotomized for processing.…”
Section: Instrumentscontrasting
confidence: 99%
“…The AQ was used in this current study to screen HC for clinically significant levels of autistic traits as it has shown to have good validity distinguishing cases from controls. However, recent studies suggest it may be less effective in predicting an autism diagnosis in clinical populations with high levels of suspected autistic traits [44][45][46]. In light of this research, the AQ was not used to categorise people with AN in this study as above or below threshold on the AQ, but rather was used as a continuous measure of autistic traits.…”
Section: Autism Quotientmentioning
confidence: 98%
“…The AQ has previously been used in AN populations, with people with AN typically scoring higher compared to HC (28). Whilst the AQ does include a cut-off score, with scores above 32 indicating potentially clinically significant levels of autistic traits, recent research has questioned the ability of the AQ to distinguish "true" autism cases in populations with high levels of autistic traits (51)(52)(53). Consequently, beyond screening HC for high autistic traits at the beginning of the study, the AQ was only used in the analysis as a continuous measure.…”
Section: Clinical Variablesmentioning
confidence: 99%